SURGICAL OUTCOME OF CORPECTOMY, BONE GRAFTING AND CASPAR PLATING IN NON-TRAUMATIC CERVICAL SPINE DISEASES - Khalid, Muhammad; Farooq, Umer; Ahmed, Ejaz; Khaleeq, Samina; Uz Zaman, Khaleeq (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine the neurological outcome in non-traumatic cervical spine diseases after corpectectomy, bone grafting and Caspar plating. Methods: Patients presenting with cervical spine diseases were included in this descriptive study. Patients' demographic profiles, symptoms, signs and imaging findings were recorded. The corpectomy was performed through anterior approach. The bone graft was taken from iliac crest. The graft was shaped according to the size and fixed in position with Caspar and screws. Post op. check x-rays were carried out to confirm the position of graft and hardware. Eighty one patients were studied during 3 years. Results: Out of 81 patients, 53 were male while 28 were female; age ranged from18 to 60 years with mean age of 43.44 ±12.52 years. 35(43.2%) patients had cervical spine stenosis secondary to osteophyte and hard disc, 15(18.5%) patients had cervical stenosis with soft discs at multiple levels, 10(12.3%) patients had ossified posterior longitudinal ligaments, 10(12.3%) patients had collapsed vertebra secondary to metastasis, 7(8.6%) patients had collapsed vertebra secondary to plasmacytoma and 4(4.9%) patients had collapsed vertebra secondary to old carries spine. Ninety percent of patients presented with neck pain, brachalgia, quadriaparesis and urinary retention. Pain was relieved in all patients (100%). Motor deficit recovered in 70 patients (86.41%). Conclusion: In our study corpectomy, bone grafting and fixation with Casper plating had a good neurological outcome in non-traumatic diseases of lower cervical spine.